A palette of site-specific organelle fluorescent thermometers. (December 2022) - Liu, Xiao; Yamazaki, Takeru; Kwon, Haw-Young; Arai, Satoshi; Chang, Young-Tae
Abstract: Intracellular micro-temperature is closely related to cellular processes. Such local temperature inside cells can be measured by fluorescent thermometers, which are a series of fluorescent materials that convert the temperature information to detectable fluorescence signals. To investigate the intracellular temperature fluctuation in various organelles, it is essential to develop site-specific organelle thermometers. In this study, we develop a new series of fluorescent thermometers, Thermo Greens (TGs), to visualize the temperature change in almost all typical organelles. Through fluorescence lifetime-based cell imaging, it was proven that TGs allow the organelle-specific monitoring of temperature gradients created by external heating. The fluorescence lifetime-based thermometry shows that each organelle experiences a distinct temperature increment which depends on the distance away from the heat source. TGs are further demonstrated in the quantitative imaging of heat production at different organelles such as mitochondria and endoplasmic reticulum in brown adipocytes. To date, TGs are the first palette batch of small molecular fluorescent thermometers that can cover almost all typical organelles. These findings can inspire the development of new fluorescent thermometers and enhance the understanding of thermal biology in the future. Graphical abstract: Thermo Greens (TGs) are the first batch of fluorescent thermometers that can cover almost all typical organelles. The FLIM thermometry shows that each organelle experiences a distinct temperature increment depending on the distance away from the heat source. TGs are further demonstrated in the quantitative imaging of the heat production at different organelles in brown adipocytes. Image 1